State-of-the-art detection of Mycobacterium tuberculosis in blood during tuberculosis infection using phage technology - Catherine ED Rees; Benjamin MC Swift; Pranabashis Haldar (International Journal of Infectious Diseases, 2024)
Introduction/Abstract: Tuberculosis (TB), an aerosol-transmitted infection caused by Mycobacterium tuberculosis (Mtb), remains the commonest cause of death globally, from an infectious bacterial disease. Nine years on from the launch of the World Health Organization (WHO)’s END-TB strategy, disease incidence rates are stubbornly unchanged [1]. While this represents, in part, a reversal of improving trends caused by the COVID-19 pandemic, it also reflects the fragility and inadequacy of healthcare systems to sustain TB control [2]. Although multifactorial, a key reason for this is the ineffectiveness of existing clinical tools to meet the two key objectives of the END-TB strategy—(i) early diagnosis and treatment of TB disease (to limit onward transmission); and (ii) disease prevention through screening for asymptomatic TB infection (TBI). Meeting both objectives will rely on the development of new biomarkers with high accuracy, but the global nature of the TB problem also requires that new tests are rapid, low cost and can be measured in patients by sampling from universally accessible sites. In this review, we will present the accumulating evidence for circulating Mtb in both TB disease and asymptomatic TBI and discuss the potential utility of novel bacteriophage-based technology for blood-based detection of Mtb.